MANAJEMEN KELAS SEBAGAI PENDUKUNG KEBERHASILAN STRATEGI PEMBELAJARAN - M. Iqodzul Himam Abil Izz; Muhammad Nur Ilham; Harits Mafaza Ahsan; Puput Rifani; Nur Lailaana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Classroom management plays a crucial role in supporting the success of the learning process. The success of learning strategies is influenced not only by the selection of appropriate methods but also by the teacher’s ability to manage the classroom. This article aims to examine the role of classroom management in supporting the success of learning strategies through a literature review. The method used is a literature review utilizing various sources, such as books, scientific journals, and articles related to classroom management and learning strategies. The results of the review indicate that effective classroom management can create a comfortable and conducive learning environment, increase student attention and engagement, reduce disruptions during learning, and help teachers implement learning strategies more effectively. Furthermore, effective classroom management can foster positive relationships between teachers and students, making it easier to achieve learning objectives. Therefore, teachers must possess and continuously develop classroom management skills to support successful learning.